Evaluación de la producción de cuatro líneas promisorias de oca (oxalis tuberosa) en aprovechamiento de diferentes niveles de Abonadura Orgánica en el sector la Esperanza, provincia Imbabura - Gualacata Pupiales, Norma Isabel (2015)
This research was conducted in the parish, La Esperanza, canton Ibarra, Imbabura province located 2430msnm. The objective was to evaluate the agronomic performance and sweet white promising lines of oca (Oxalis tuberosa), sweet yellow, string beans, sweet pink and doses of vermicompost. The production of four promising lines oca (Oxalis tuberosa) in use at different levels of organic abonadura was evaluated. The variables evaluated were: number of emerged at 20 days after planting plants; Plant height at the beginning of flowering, length, diameter, average tuber weight, days to harvest, yields expressed in tonnes / Ha, and cost benefit. Complete block design was used in combinatorial analysis boost factorial arrangement with 12 treatments, three repetitions .The treatment comparison is performed with Tukey 5%. Best yields the white goose treatment chaucha averaging 24 25.64 12 t / ha with humus applications in 2500 and 2000 kg dose / ha was obtained. According to the results of the financial analysis, the treatments were sweet white goose and fuck that generates a cost benefit ratio 2.31y 2.40 respectively.